Preimplantation Genetic Testing of Multiple Endocrine Neoplasia Type 2A - Würgler Hansen, Anders; Sønderberg Roos, Laura Kirstine; Løssl, Kristine; Godballe, Christian; Mathiesen, Jes Sloth (Frontiers in Endocrinology, 2020)
Background: When discussing matters of reproduction, the 2015 revised guidelines for the management of medullary thyroid carcinoma recommend that patients diagnosed with multiple endocrine neoplasia type 2A (MEN 2A) are informed about the option of Preimplantation Genetic Testing for Monogenic Disorders (PGT-M). In addition, patients seem to have a genuine interest in reproductive options. However, there are just two reports worldwide of this technology being used for patients with MEN 2A. We here present, in a Danish couple where the man has MEN 2A, the first European family with children born after PGT-M. Objective: To report the results of PGT-M in relation to multiple endocrine neoplasia type 2A with the aim to increase awareness among physicians treating this and other genetic disorders. Methods: A Danish couple was referred to the PGT Centre at Copenhagen University Hospital Rigshospitalet and opted for PGT-M after counseling by a clinical geneticist and a fertility doctor. The embryos were diagnosed using microsatellite polymorphic marker close to RET. Results: The couple had two healthy children born in 2017 and 2019 as a result of a total of three ICSI treatments including controlled ovarian stimulation, oocyte retrieval and PGT-M, and a total of six blastocyst transfers. Conclusion: A session with a clinical geneticist covering all reproductive options for patients in early adult life is a relevant part of the clinical management of patients with MEN 2A, and other patients with hereditary cancer predisposition syndromes.